A Case Report of Retroperitoneal Ectopic Pregnancy After in vitro Fertilization-Embryo Transfer and Literature Review - Liu Z; Jing C (Dove Medical Press, 2023)
Zesi Liu,1 Chunli Jing2 1Department of Gynecology and Obstetrics, The First Affiliated Hospital of Dalian Medical University, Dalian, People's Republic of China; 2Department of Ultrasound of Gynecology and Obstetrics, The Second Affiliated Hospital of Dalian Medical University, Dalian, People's Republic of ChinaCorrespondence: Chunli Jing, Department of Ultrasound of Gynecology and Obstetrics, The Second Affiliated Hospital of Dalian Medical University, Dalian, People's Republic of China, Tel +86-133-522-31070, Fax +86-82866055, Email tg980927@126.comBackground: Retroperitoneal ectopic pregnancy (REP) is an extremely rare type of ectopic pregnancy that can be life threatening. The pathogenesis of REP remains inconclusive and the diagnosis and treatment modalities are unclear.Case Presentation and Review of the Literature: A 27-year-old woman (gravida: 3; parturition: 0) underwent transvaginal ultrasound (TVS) 40 days after in vitro fertilization-embryo transfer (IVF-ET); no intrauterine gestational sac was detected. The patient was asymptomatic and had no abnormalities on physical examination. β-HCG and progesterone were 18.210 mIU/mL and 10.891 ng/mL, respectively. Transabdominal ultrasound (TAS) showed that the gestational sac had implanted adjacent to the abdominal aorta and near a branch of the iliac artery. Laparoscopic exploration was performed under general anesthesia; intraoperative findings showed that the gestational sac was approximately 2.5 cm in diameter and in the same location as suggested by preoperative ultrasound. Histopathological examination confirmed the diagnosis of EP. On day three post-surgery, the levels of β-HCG had fallen to 911 mIU/mL. We further systematically reviewed the REP cases reported in the English literature and performed a review on the diagnosis and treatment of REP.Conclusion: Clinicians should be alert to the occurrence of REP. Combined radiological examinations including ultrasonography (TAS and TVS), CT, and MRI are essential for the early diagnosis of REP. Once a definitive diagnosis is made, appropriate treatment should be administered immediately. Although there are cases of successful drug treatment described in the literature, surgery remains as the primary treatment option for REP.Keywords: retroperitoneal ectopic pregnancy, ultrasound, surgery, diagnosis, review